OCHRONA DANYCH OSOBOWYCH JAKO ELEMENT PRAWA DO PRYWATNOŚCI - Sobczyk, Paweł (Zeszyty Prawnicze, 2017)
Personal Data Protection as Part of the Right to Privacy Summary The issues related to the right to privacy and personal data protection are a new important area for the constitutional studies in Poland. Their emergence owes much to the development of information technology and the adjustment of Polish law, including constitutional law, to international standards. Under the Constitution of the Republic of Poland of 2 April 1997, personal protection is seen as part of the right to privacy. The following issues have become the subject of the academic research: the constitutionalization of personal data protection, constitutional rights of identifiable persons, the relation of personal data and the right to privacy, the democratic state under the rule of law as the guarantor of the right to privacy and personal data protection, as well as human dignity as the basis of this right.